2017
DOI: 10.3390/nu9010052
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxy-Vitamin D Concentration Is Not Affected by Severe or Non-Severe Pneumonia, or Inflammation, in Young Children

Abstract: Poor vitamin D status has been associated with increased risk and severity of respiratory tract infections. Whether or not inflammation and infection affects 25-hydroxy vitamin D (25(OH)D) concentration is controversial and is important in the interpretation of observational studies using plasma-25(OH)D as a biomarker for status. Our objectives were to measure whether 25(OH)D concentration was altered by an episode of acute lower respiratory tract infection and whether markers of inflammation predicted the 25(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
3
15
1
1
Order By: Relevance
“…We did not include a healthy control group in this study, but we have data on vitamin D status in young children in the same area, both in children with less-severe pneumonia (28) and in healthy infants (31). In the study of children with lesssevere pneumonia the percentage of children with vitamin D insufficiency and deficiency was comparable to the findings in this study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We did not include a healthy control group in this study, but we have data on vitamin D status in young children in the same area, both in children with less-severe pneumonia (28) and in healthy infants (31). In the study of children with lesssevere pneumonia the percentage of children with vitamin D insufficiency and deficiency was comparable to the findings in this study.…”
Section: Discussionmentioning
confidence: 49%
“…In a recent publication in children with bacterial illness, no difference was found between 25(OH)D concentration during bacterial infection and 4 weeks later, and the authors concluded that an acute alteration in vitamin D status seemed unlikely, but they also acknowledged the problem that no pre-infectious samples were taken. Further, in a sample of young Nepalese children, we demonstrated that 25(OH)D concentration was not affected by clinical infection or inflammation (28).…”
Section: Discussionmentioning
confidence: 66%
“…This study found an interesting gender association, with males exhibiting a higher incidence of severe CAP. However, Haugen et al studied 420 children with nonsevere and severe CAP but did not observe this gender association. This disagreement suggests that new studies with higher numbers of subjects are necessary to resolve the relevance of gender as a risk factor.…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, serum 25(OH)D levels among the cases was determined only during hospital admission, after the onset of COVID-19 symptoms. However, prior research shows that blood vitamin D level is stable, and not affected by acute respiratory infection (37), so the 25(OH)D level at admission most probably reflects the level before infection.…”
Section: Strengths and Limitationsmentioning
confidence: 98%